The Impact of Intangible Factors on the Employees of Educational Institutions - Vanagas, Ramūnas; Urmanavičienė, Audronė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The goal of this article is to explore the motivation and the factors for the motivation, to discuss the impact of intangible factors for the motivation of educational staff (teachers) for their work efficiency. In order to achieve these goals we have set the following tasks: to define the concept of motivation by analysing scientific literature; and to establish the determinant factors for the motivation of teachers. Motivation is a complex phenomenon, related to the promotion of behaviour, actions and efficient activities. Motivation of teachers is a part of the general strategy of a school, which is influenced by the headmaster, the administration of the school, the attitude of the staff and the created conditions for a teacher to work successfully and to apply innovative methods in their work and to feel responsible for the development of personality.